Respuesta :
Answer:
y=(1/7)*x+(15/7)
Step-by-step explanation:
first, lets find the slope:
m=(y2-y1)/(x2-x1)
m=(3-2)/(6-(-1))
m=1/7
y=(1/7)*x+b
to find b lets pug in a point we know into the equation:
3=(1/7)*6+b
21/7=6/7+b
b=(21/7)-(6/7)
b=15/7
now we know the equation in slope intercept form representing this function is:
y=(1/7)*x+(15/7)
Answer:
y= 1/7x+15/7
Step-by-step explanation:
points
(-1, 2) and (6, 3)
slope intercept form:
- y= mx+b
2= -m+b, 3= 6m+b ⇒ m= 1/7 ⇒ b= 2 1/7= 15/7
- y= 1/7x+15/7